PENGARUH STRATEGI PEMBELAJARAN INQUIRY TERHADAP KARAKTER DISIPLIN PESERTA DIDIK PADA MATERI SOLAT SUNNAH DHUHA KELAS VII B DI MTSN 3 KARAWANG - Septiani, Devi; Bariah, Oyoh; Makbul, M. (LPPM STAI Muhammadiyah Probolinggo, 2024)
Education is a fundamental need for humans. The achievement of learning objectives is determined by both the students and the teachers. Teachers' ability to deliver learning materials through the selection of appropriate media, methods, or learning strategies creates an enjoyable learning environment and can foster students' disciplined character for studying. Therefore, this research aims to investigate the effect of inquiry-based learning strategies on students' disciplined character. The study was conducted at MTSN 3 Karawang for grade VII B in the subject of the sunnah dhuha prayer. The method used in this research is a quantitative approach with a correlational method and a field research design using purposive sampling. The population consisted of 128 students, and a sample of 30 students was selected using non-probability sampling. Data collection techniques included questionnaires, documentation, and data analysis through descriptive and inferential statistical analysis, with the data processed using SPSS version 25. The data analysis results obtained through SPSS calculations showed a correlation between inquiry-based learning strategies and students' disciplined character in the sunnah dhuha prayer subject for grade VII B at MTSN 3 Karawang. The hypothesis test results using simple regression analysis at a 0.05 significance level through SPSS version 25 yielded a result of 0.000 < 0.05, indicating that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Based on the R square value, a value of 38.4% was obtained. Therefore, it can be concluded that there is an effect of using inquiry-based learning strategies on students' disciplined character by 38.4%.Keywords: Inquiry-Based Learning Strategies; Students Disciplined Character; Sunnah Dhuha Prayer .